Sprężysto-Plastyczna Deformacja i Pełzanie Powłoki Kulistej - Bychawski, Z.; Kopecki, H. (Engineering Transactions, 1967)
In a few recent papers [1] to [4] one of the present authors has obtained some solutions for a plane membrane circular and plane membrane of any contour. These solutions concerned elastic-plastic instantaneous and creep deformation in the geometrically nonlinear range. The solutions for creep were obtained on the grounds of the physical-geometrical analogy given by the author. General solution of the composite problem of instantaneous deformation and creep of plane circular membranes was found by the present authors in [5]. The solution methods applied in the works just mentioned can also be applied in cases of composite deformation of geometrically nonlinear shells of revolution in a membrane state. The general idea of solution is described for a composite state of an elastic-plastic and creep deformation of a spherical shell of small rise in the range of large deflections. The fundamental solution for all the particular cases of instantaneous deformation is analysed in detail. It is found that the analogy formulated by one of the present authors finds application to shells of revolution in the membrane state for pure creep also. On the basis of this analogy a physically justified and admissible solution of the problem is found in a simple manner. As a particular case is considered a shell of a perfectly plastic material, for which solution is obtained by elementary methods. It is shown that the special cases of a linearly-elastic shell and a plane membrane can be obtained from the solutions given by the authors and coincide with the results obtained in [1-5].